BMP-2 Expression Correlates with Local Failure in Head and Neck Squamous Cell Carcinoma. (February 2014) - Sand, Jordan P.; Kokorina, Natalia A.; Zakharkin, Stanislav O.; Lewis, James S.; Nussenbaum, Brian
Objective: Preclinical data show that exogenous administration of recombinant human bone morphogenetic protein-2 (rhBMP-2) to human oral carcinoma cell lines increases pathogenicity using a nude mouse model. The objectives of this study are to (1) describe the characteristics of baseline protein expression of BMP-2 in head and neck squamous cell carcinomas (HNSCC) and (2) determine if BMP-2 expression level correlates with worse oncologic outcomes. Study Design: Retrospective analysis of previously harvested patient samples. Setting: Academic medical center. Subjects: In total, 149 patients with oral cavity, oropharynx, larynx, and hypopharynx HNSCC treated between January 1, 1997, and December 31, 2004. Methods: A tissue microarray of HNSCC was assembled and immunohistochemistry for BMP-2 performed. Staining was quantified using a standardized scoring system. Specimens were dichotomized into high or low expression level. Statistical analyses using log-rank, Wilcoxon, and Fisher exact test were performed for associations between BMP-2 protein level and clinicopathologic features and patient survival. Results: BMP-2 expression at any level was noted in 146 of 149 (98%) of samples. Tumors with high BMP-2 expression had higher rates of local failure compared with low-expressing tumors (17.3% vs 6.3%; P = .04). There was no significant association for BMP-2 expression level with tumor location, T stage, N stage, overall survival, regional failure, or distant failure. Conclusion: Head and neck squamous cell carcinomas with high baseline BMP-2 protein level are associated with higher rates of local recurrence. These data have important implications for using rhBMP-2 in tissue engineering reconstructive approaches in the setting of cancer-related defects.